Designing for Homeless in Kuala Lumpur: Concepts and Case Studies - Noor Hisham, Nadiyah; Md Amin, Noor Dina (International Journal of Integrated Engineering, 2024)
Homelessness issue in Kuala Lumpur has no permanent solution. There are current needs to provide definite helps and solutions. This paper aims to identify and explore the concepts and ideas in providing shelter for the homeless in Kuala Lumpur. A qualitative and conventional content analysis of narrative data is implemented to achieve the research aim. Series of case studies explains the concepts and ideas that may be implemented as part of the possible solutions in providing shelter for the homeless in Kuala Lumpur. This study will hopefully provide significant finding that may be applied towards designing a proper basic community shelter for the homeless in Kuala Lumpur.